Association between inflammatory cytokines and long-term adverse outcomes in acute coronary syndromes: A systematic review. Issue 4 (April 2020) - Kristono, Gisela A.; Holley, Ana S.; Lakshman, Prashant; Brunton-O'Sullivan, Morgane M.; Harding, Scott A.; Larsen, Peter D.
Abstract: Background: Inflammatory cytokines are involved in the pathophysiology of acute coronary syndromes (ACS) and have been associated with major adverse cardiovascular events (MACE). We systematically reviewed studies investigating the ability of multiple cytokines to predict MACE in ACS patients with follow-up of at least one year. Methods: A Medical Subject Heading search criteria was applied on Ovid Medline(R), EMBASE, EMBASE Classic and Cochrane Library to systematically identify relevant studies published between 1945 and 2017 that had an observational study design or were randomised controlled trials. Studies were excluded if only one cytokine was analysed, follow-up period was less than one year, subjects were non-human, or blood samples were taken more than 10 days from symptom onset. Results: Ten observational studies met the inclusion criteria. Six had acceptable internal validity when evaluated for quality. The studies were varied in terms of study methods (time of blood collection, study population, cytokines assessed, MACE definition, follow-up length) and result reporting, so a meta-analysis could not be conducted. Six of the studies found significant associations between individual cytokines and MACE. Four studies measured the combined effects of multiple cytokines to predict MACE, and all had statistically significant results. Conclusion: A combination of multiple cytokines had a better association with MACE than individual cytokines. It appears promising for future studies to determine the optimal multi-marker methodology and confirm its predictive value. Abstract : Clinical research; Cardiology; Inflammation; Health sciences; Biomarkers; Outcomes; Acute coronary syndromes; Cytokines